2005
DOI: 10.1007/s00330-005-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic multi-section CT imaging in acute myocardial infarction: preliminary animal experience

Abstract: To evaluate the feasibility of myocardial first-pass perfusion imaging with multidetector CT (MDCT). In five pigs, myocardial infarction was induced by permanent balloon occlusion of the left anterior descending coronary artery. Dynamic contrast-enhanced MDCT (12x1.5 mm, 120 kV, 30 mAs, 64 acquisitions, 40 ml iopromide 370@4 ml/s) and contrast-enhanced first-pass perfusion magnetic resonance (MR) imaging (TR 7.7 ms/TE 2.6 ms, 64 acquisitions, 0.05 mmol/kg Gd-DTPA) were performed. Finally, the animals were sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 20 publications
1
46
0
1
Order By: Relevance
“…dimensional coverage, high spatial resolution, and excellent contrast between the myocardium and blood pool. Retrospectively, electrocardiographically gated multidetector CT has been used to quantify LV volumes, ejection fraction, and contractility ( 48 ). Our fi ndings indicate that global LV functional measurements-namely, ejection fraction, end-diastolic volume, end-systolic volume, and cardiac output-quantifi ed on multidetector CT images are comparable with those quantifi ed on the reference standard MR images.…”
Section: Practical Applicationsmentioning
confidence: 54%
“…dimensional coverage, high spatial resolution, and excellent contrast between the myocardium and blood pool. Retrospectively, electrocardiographically gated multidetector CT has been used to quantify LV volumes, ejection fraction, and contractility ( 48 ). Our fi ndings indicate that global LV functional measurements-namely, ejection fraction, end-diastolic volume, end-systolic volume, and cardiac output-quantifi ed on multidetector CT images are comparable with those quantifi ed on the reference standard MR images.…”
Section: Practical Applicationsmentioning
confidence: 54%
“…Data on the accuracy of coronary artery assessment is rapidly evolving, with many articles showing high sensitivity and specificity for detection of substantial coronary artery stenosis by using multidetector CT as compared with invasive coronary angiography (3)(4)(5)(6)(7). While promising reports on ventricular function (8)(9)(10)(11)(12) and infarct imaging by using multidetector CT (13)(14)(15)(16) have been published, data on global LV function, regional wall motion (RWM), and PD assessment with multidetector CT in the acute MI setting are somewhat limited. If these assessments can be reliably obtained by using multidetector CT, it may provide an excellent tool for the rapid noninvasive diagnostic and prognostic evaluation of patients with acute MI.…”
mentioning
confidence: 99%
“…Using several parameters derived from TACs, they compared infarcted and normal myocardium and demonstrated significant differences in the maximum attenuation density, time to maximum attenuation density, and upslopes of the myocardial TACs. 39 Furthermore, they showed that the area at risk as evident on gross pathology (in triphenyltetrazolium chloride-stained specimens) corresponded well to hypoperfused areas noted on CT-MPI. 39 So et al, in a porcine model of acute myocardial infarction, performed quantitative myocardial perfusion and showed that perfusion measurement of MBF with dynamic CT was accurate and correlated well with histology and microsphere measurements.…”
Section: Dynamic Ct-mpimentioning
confidence: 88%
“…39 Furthermore, they showed that the area at risk as evident on gross pathology (in triphenyltetrazolium chloride-stained specimens) corresponded well to hypoperfused areas noted on CT-MPI. 39 So et al, in a porcine model of acute myocardial infarction, performed quantitative myocardial perfusion and showed that perfusion measurement of MBF with dynamic CT was accurate and correlated well with histology and microsphere measurements. 40 George et al, using a 64-detector CT in a canine ischemia model, performed CT-MPI during adenosine infusion.…”
Section: Dynamic Ct-mpimentioning
confidence: 88%